Drawn Visions. Athanasius Kircher's research between interpretation and resolution of reality (diségno, 2021)
The figure of the German Jesuit Athanasius Kircher (1602-1680) is significant within the graphic culture emerging in 17th century Europe. His writings, richly drawn, and his research, in the whole Baroque spirit, are strongly characterised using hermetic and neo-Platonic philosophies. These become an opportunity to build a bridge between medieval systems of thought and the growing empirical movement of the scientific revolution. The essay aims to demonstrate the richness of Kircher's study, capable on the one hand of grasping the connections of a nascent scientific thought and on the other of pushing the imaginative power of drawing to its limits. This dual nature –of science and representation– is investigated by bringing out the role of drawing in the representation of reality. Where what can be directly observed coexists on the same plane with what can only be imagined. The research highlights the crucial passage between the dimension of the circle and that of the ellipse. The former represents the certainty of the Renaissance man, the latter –Kircher's one– highlights the unstable and dialectical nature of Baroque knowledge. It is precisely in the shadows of the Jesuit's thought that we rediscover the connective power of his thinking, which is most evident in the visionary dimension of his drawings.
Keywords: Kircher; iconisms; visionary drawing